Integrated negative pressure wound therapy system with volumetric automated fluid instillation in wounds at risk for compromised healing - Gabriel, Allen (Int Wound J, 2012)
Nearly all wounds are at risk for compromised healing due to excessive exudation, oedema, contaminants and presence of inflammatory mediators. Compromised wounds have the potential to develop complications, such as infection, which may lead to delayed wound healing, prolonged hospitalisation and more frequent readmissions. It is generally believed that the wound advances from contamination to colonisation when the bacteria on the wound's surface begin to replicate and increase their metabolic activity. Heavy bacterial bioburden increases the metabolic requirements, stimulates a proinflammatory environment and encourages the in‐migration of monocytes, macrophages and leukocytes – all of which can negatively impact wound healing. Bacteria also secrete harmful cytokines which can lead to vasoconstriction and decreased blood flow. Thus, controlling or preventing infections is essential for normal wound healing process to occur. While the mainstay of treating wound infection has historically included intravenous, oral and/or topical antimicrobials in addition to frequent gauze dressing changes, a shift towards wound management with advanced modalities, such as negative pressure wound therapy (NPWT), has occurred during the past decade. This review will provide expert opinion and scientific support for the use of NPWT with instillation (NPWTi; V.A.C. Instill® Wound Therapy and V.A.C. VeraFlo™ Therapy, KCI USA, Inc., San Antonio, TX) for the treatment of at‐risk and complicated wounds.